2019
DOI: 10.1002/ijgo.12788
|View full text |Cite
|
Sign up to set email alerts
|

Women's experience with group prenatal care in a rural community in northern Nigeria

Abstract: Objective To assess women's experience of group prenatal care in a rural Nigerian community. Methods In an observational study, consenting pregnant women were enrolled in a group prenatal care program based on the CenteringPregnancy model from July 1, 2010, to June 30, 2011, in Tsibiri, Nigeria. Women were interviewed before joining the group and postnatally. A predesigned pro forma was used to assess group behavior during sessions. Descriptive and inferential statistics were applied to data. Results In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…Many commented on their appreciation for the social element of G-ANC and referenced the relationships developed in this model as promoting a sense of support and engagement both within and beyond the antenatal care context. These findings are consistent with studies of G-ANC participants in LMIC settings [7,8,11,[37][38][39], and of adolescent G-ANC participants specifically in high-income settings [12,17,18]. Previous studies have not explicitly examined adolescents' perspectives on being a part of a "mixed-age" G-ANC group, and the optimal composition of G-ANC groups remains a topic of interest within the literature.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Many commented on their appreciation for the social element of G-ANC and referenced the relationships developed in this model as promoting a sense of support and engagement both within and beyond the antenatal care context. These findings are consistent with studies of G-ANC participants in LMIC settings [7,8,11,[37][38][39], and of adolescent G-ANC participants specifically in high-income settings [12,17,18]. Previous studies have not explicitly examined adolescents' perspectives on being a part of a "mixed-age" G-ANC group, and the optimal composition of G-ANC groups remains a topic of interest within the literature.…”
Section: Discussionsupporting
confidence: 83%
“…In low-and middle-income countries (LMIC), G-ANC is associated with improved health literacy, higher patient satisfaction and increased facility-based delivery [2,[6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…Five quantitative studies reported various SC outcomes related to parents' connections to their community, that is, parents' reported perceptions of or interactions with their communities or neighborhoods, and related resources (Acri et al, 2019;Adaji et al, 2019;Brisson, 2012;Brisson et al, 2019;Yuma-Guerrero et al, 2017). Yuma-Guerrero et al…”
Section: Connection To Communitymentioning
confidence: 99%
“…reported low-income families participating in the intervention, "Your Family, Your Neighborhood," designed to improve neighborhood social cohesion, showed improvements in SC (framed as "neighborhood social cohesion"). However, these improvements were not significantly greater than those in a comparison groupF I G U R E 1 Review process T A B L E 2that did not receive the intervention Adaji et al (2019). found SC formed during a prenatal care program in Nigeria to be associated with better program outcomes as mothers who participated in the program had higher levels of SC (framed as "group cohesion") and increased knowledge in pregnancy issues at the end of the program.…”
mentioning
confidence: 99%
“…A large cluster-randomized trial in Nigeria and Kenya found greater antenatal care attendance in both countries and more birth planning for a facility-based birth in Nigeria [52,53]. Two smaller studies in Nigeria with weaker designs reported greater attendance, greater knowledge of danger signs, and more use of health facilities for delivery [54,55]. Importantly, these initiatives do not report sufficient detail about if and in what ways their models deviate from the evidence-based CenteringPregnancy model (i.e., fidelity).…”
Section: Introductionmentioning
confidence: 99%